Mid- and High-Frequency Oscillation Suppression Strategy for MMC-HVDC System Based on DC Current Feedback - Yechun XIN; Shangxuan LI; Yanxu WANG; Yihua ZHU; Jiawei YU; Dongxu CHANG (Zhongguo dianli)
The serious mid-and high- frequency oscillation issue in modular multilevel convertor based high voltage direct current (MMC-HVDC) systems poses a significant threat to the normal operation of power systems. In this paper, we firstly established an AC-side impedance model of the MMC based on its dynamic phase vector model. Secondly, we analyzed the impact of control loops and control parameters on MMC impedance characteristics using the impedance method, and identified the power outer loop, current inner loop and control loop delay as the main factors causing MMC to present negative damping characteristics. And then, based on an analysis of the limitations of existing oscillation suppression strategies that are based on voltage feedforward loops and current inner loops, we proposed an oscillation suppression strategy that adds DC current feedback to the power outer loop, which can greatly eliminate harmonic components in the system and improve MMC impedance characteristics. Finally, the correctness and effectiveness of the theoretical analysis and proposed suppression measures were verified through electromagnetic simulation software.